Role of Micro-credit in Poverty Alleviation of Rural Poor: Evidence from Laxmipur District of Bangladesh - Karim, Md Rezaul; Tania, Shamsunnahar; Farazi, Md Mansur Rahman (Journal of Business and Technology (Dhaka), 2013)
This paper examines the role of microcredit as a tool to fight poverty. Bangladesh Government and Non-Government Organizations (NGOs) have been trying to alleviate poverty of its people. NGOs provide microcredit to poor people to enhance their income and improve the situation of hardship. This study takes up the Laxmipur experience of Bangladesh. The study reveals that microcredit programs have generated positive results for large numbers of the poor. Micro-credit has significant impacts and ensures the food security. The poor are not homogeneous, so impact varies significantly among different segments of the population according to their socio-economic status, gender, background, family composition and others. The analysis shows that in general, the poorest borrowers benefit less compared to the middle level poor. Microcredit is not the only way out for all the poor for alleviating their poverty. Our analysis shows that microcredit alone cannot alleviate the poverty significantly without ensuring their individual transactional powers such as economic transaction, social transaction, legal transaction and political transaction power. DOI: http://dx.doi.org/10.3329/jbt.v7i2.16453 Journal of Business and Technology Vol.7(2) 2012: 37-55